Limited use only. How can the design of an everyday object help chronic stroke patients to overcome the learned nonuse of the upper limb?. (28th July 2017) - Lemke, Mailin; Rodríguez Ramírez, Edgar; Robinson, Brian
Abstract: Stroke causes significant damage to the brain and symptoms commonly affect one or both limbs on one side of the body. Compensatory movement is the preferential use of the non-affected limb and is a common phenomenon after a stroke, leading to a learned nonuse of the affected side. This learned nonuse of an upper limb can be overcome through constraint induced movement therapy (CIMT) during which the non-affected arm is physically restrained to enhance the use of the affected arm. This paper presents the outcomes of a design course with undergraduate students in which the students developed design solutions based on CIMT components that encourage the use of the affected arm. Six design solutions were evaluated by therapists with experience in stroke rehabilitation. Their feedback indicates that the designs have the potential to be used in a self-directed way by stroke survivors and that they contain a therapeutic value.